Composition, abundance and diversity of the Family Cichlidae in Oyan Dam, Ogun State, Nigeria - OLANIYI ALABA OLOPADE; OLUSEUN PETER RUFAI (Biodiversitas Journal of Biological Diversity, 2014)
Olopade OA, Rufai OP. 2014. Composition, abundance and diversity of the Family Cichlidae in Oyan Dam, Ogun State, Nigeria. Biodiversitas 15: 195-199.This study was conducted to determine status of the family Cichlidae in Oyan Dam, Nigeria, during the wetand dry seasons of 2011. Samples were collected using multi-mesh gillnets ranging between 30 mm to 80 mm. Simpson's DiversityIndex was used to determine the species richness, while dominance and evenness were given by Shannon's index. A total of 547individuals were caught from Imala (S1) and Ibaro (S2) sites of the dam. Species collected include Sarotherodon galilaeus (42.60%),Oreochromis niloticus (17.92%), Tilapia zillii (25.41%), Hemichromis fasciatus (10.61%) and Tilapia mariae (3.48%). Juveniles andsub-adults and adults were among the catch, the sizes were as big as 12.85±0.29cm SL, 109.22±6.00g BW in Tilapia zillii and small as6.09±0.05cm SL and 8.07±0.15g BW in Hemichromis fasciatus. The diversity indexes showed that the diversity of Cichlids was lowerin the two sites observed in Oyan Dam. The estimates of diversity indexes showed lower value for site 1 (0.284) than for site 2 (0.294);Simpson's diversity index was 0.716 for site 1 and 0.703 for site 2 while reciprocal indexes for site 1(3.521) was slightly lower than site2 (3.367). Shannon-Wiener’s Index recorded in the site 1 (1.36) was slightly lower than site 2 (1.37). Pielou’s Index value recorded forsite 1 was 0.845 and 0.852 for site 2. Sarotherodon galilaeus, Oreochromis niloticus, Tilapia zillii and Tilapia mariae exhibited apositive allometric growth pattern while only Hemichromis fasciatus showed a negative allometric growth.